Performance Assessment of Bridgeless Zeta Converter and Solar Energized Zeta Converter Based ACS (Journal of Scientific Research, 2025)
Two important factors to promote energy conservation are to reduce carbon footprint and excessive burden on distribution system. Air conditioning system (ACS) is one such application which is used to provide human comfort and uses excessive energy. In this paper, two configurations namely (one with bridgeless converter and other with solar energy energized converter) are considered for the ACS to reduce losses and promote alternate energy usage. In solar based ACS, Sunlight is tracked and transformed into electrical energy, which is fed to the converter for achieving steady voltage and provided to the inverter that is connected to motor. To determine the feasibility of both the ACSs, these are simulated using MATLAB/Simulink and results are recorded under a range of performance characteristics including torque and speed.